2020
DOI: 10.1002/ecy.3135
|View full text |Cite
|
Sign up to set email alerts
|

Consumer–resource dynamics in Arctic ponds

Abstract: Population dynamics are shaped by species interactions with resources, competitors, enemies, and environmental fluctuations that alter the strength of these interactions. We used a food web approach to investigate the population dynamics of an abundant Arctic mosquito species, Aedes nigripes (Diptera: Culicidae). Specifically, we evaluated the importance of bottom-up variation in aquatic biofilms (food) and top-down predation from diving beetles (Colymbetes dolabratus, Coleoptera: Dytiscidae) on mosquito popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 85 publications
(124 reference statements)
0
11
0
Order By: Relevance
“…In 2018, emerging adults varied as much as tenfold among sites, for example, the average density of emerging adults was 244 versus 24 at ponds 1a and 4, respectively (Figure 1b). Ponds with more early instar adults tended to have the most emerging adults (Figures S2 and S3, DeSiervo et al, 2020). The sex ratio of emerging males and females was approximately 1:1, with little variation among ponds (DeSiervo et al, 2020).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…In 2018, emerging adults varied as much as tenfold among sites, for example, the average density of emerging adults was 244 versus 24 at ponds 1a and 4, respectively (Figure 1b). Ponds with more early instar adults tended to have the most emerging adults (Figures S2 and S3, DeSiervo et al, 2020). The sex ratio of emerging males and females was approximately 1:1, with little variation among ponds (DeSiervo et al, 2020).…”
Section: Resultsmentioning
confidence: 89%
“…habitats, selective pressure for strong flight capacity and long dispersal distances (Smith et al, 2009(Smith et al, , 2015. number of eggs for A. albopictus), (Costanzo et al, 2018, DeSiervo et al, 2020. A. nigripes females also have a larger body mass compared to A. albopictus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Schrama et al (2018), insect predator presence decreased mosquito larval survival and adult emergence by 20-50%. Many aquatic insects of the orders Coleoptera (DeSiervo et al 2020), Diptera (Moirangthem et al 2018), Hemiptera (Allo and Mekhlif 2019) and Odonata (Córdoba-Aguilar et al 2021) are known to be mosquito predators, commonly found with the mosquito immature in varied mosquito larval habitats including the wetland (Kumar 2009;Shaalan and Canyon 2009).…”
Section: Introductionmentioning
confidence: 99%